Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 9 - Review: 7



Work Step by Step

We know that $(h\circ g)(x)=h(g(x))$. Therefore, $(h\circ g)(2)=h(g(2))=h(2+1)=h(3)=3^{3}-3^{2}=27-9=18$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.